2018
DOI: 10.15666/aeer/1603_33333350
|View full text |Cite
|
Sign up to set email alerts
|

GROWING SPINACH (Spinacia oleracea L.) IN A FLOATING SYSTEM WITH DIFFERENT CONCENTRATIONS OF NUTRIENT SOLUTION

Abstract: Abstract. This study was conducted in a greenhouse in Izmir/Turkey during the winter-early spring of 2016-2017, on spinach grown in the floating water culture system. Cultivation was carried out in aerated nutrient solutions on seedling trays, and peat was used as germination and rooting medium. Each seed was inserted to each hole (17 cc) in trays with 210 cells (957 plant m -2). Following germination in the germination chamber, trays were moved to climate controlled greenhouse. After emergence, the seedlings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 8 publications
6
12
0
Order By: Relevance
“…Foliar Mg concentrations decreased with increased K dose, but were more than adequate for spinach growth at 0.25 K, according to others [31,35] at 5.0 K. Fertilized spinach was reported to maintain high ratios of sum of cations over sum of anions, under 100 mM NaCl (EC w = 10 dS m −1 ), in the vacuole (3.2), cytoplasm (2.8), and apoplast (1.1) compared with control salinity (4.5, 2.3, and 1.2, respectively) [17], explaining why our spinach plants maintained good levels of K and Mg, under 120 mM NaCl. Although our foliar concentrations of Ca were similar as reported for spinach cultivated with full-and half-strength Hoagland's nutrient solution [31]), plants still had Na-induced Ca decrease of 32-54% (Figure 3d,j), as reported for plants in general [2,39].…”
Section: Mineral Shoot Composition In Response To Nacl and K Dosesmentioning
confidence: 59%
See 3 more Smart Citations
“…Foliar Mg concentrations decreased with increased K dose, but were more than adequate for spinach growth at 0.25 K, according to others [31,35] at 5.0 K. Fertilized spinach was reported to maintain high ratios of sum of cations over sum of anions, under 100 mM NaCl (EC w = 10 dS m −1 ), in the vacuole (3.2), cytoplasm (2.8), and apoplast (1.1) compared with control salinity (4.5, 2.3, and 1.2, respectively) [17], explaining why our spinach plants maintained good levels of K and Mg, under 120 mM NaCl. Although our foliar concentrations of Ca were similar as reported for spinach cultivated with full-and half-strength Hoagland's nutrient solution [31]), plants still had Na-induced Ca decrease of 32-54% (Figure 3d,j), as reported for plants in general [2,39].…”
Section: Mineral Shoot Composition In Response To Nacl and K Dosesmentioning
confidence: 59%
“…A stable or increased shoot N concentration was also previously reported for Jerusalem artichoke (Helianthus tuberosum L.) and alfalfa (Medicago sativa L.) cultivated in sand and with waters of increased salinity [33,34]. Regarding P, all our plants accumulated P at 4.8 to 6.7 g kg −1 ('Raccoon') and at 3.9 to 5.7 g kg −1 ('Gazelle') ( Figure 3b,h), above adequate for growth [35] and slightly under concentrations (7.7 to 10 g kg −1 ) reported for hydroponic spinach [31] and slightly above shoot-P concentrations for spinach irrigated with similar salinity treatments combined with five N doses [32]. Although salinity had no effect on shoot-P concentration, increased K reduced it significantly, albeit not enough to affect biomass accumulation.…”
Section: Mineral Shoot Composition In Response To Nacl and K Dosesmentioning
confidence: 66%
See 2 more Smart Citations
“…On the other hand, extremely high nutrient solution concentration (NSC) causes osmotic stress, ionic toxicity, and growth restriction [27]. Several studies have demonstrated that NSC influences the growth and components of spinach, tomato, cucumber, salvia, bean, artichoke, wasabi, and lettuce plants [28][29][30][31][32][33][34][35][36][37]. In a hydroponic NSC with high electrical conductivity (EC), the growth of tomato plants was restricted, whereas the level of sugars and lycopene in tomato fruits, and consequently fruit quality, were enhanced [30].…”
Section: Introductionmentioning
confidence: 99%